Varietal Identification in Household Surveys : Results from an Experiment Using DNA Fingerprinting of Sweet Potato Leaves in Southern Ethiopia - Kosmowski, Frederic; Aragaw, Abiyot; Kilian, Andrzej; Ambel, Alemayehu; Ilukor, John; Yigezu, Biratu; Stevenson, James (World Bank, Washington, DC, 2016)
Sweet potato (Ipomoea batatas) varieties have important nutritional differences and there is strong interest to identify nutritionally superior varieties for dissemination. In agricultural household surveys, this information is often collected based on the farmer's self-report. However, recent evidence has demonstrated the inherent difficulties in correctly identifying varieties from self-report information. This study examines the accuracy of self-report information on varietal identification from a data capture experiment on sweet potato varieties in southern Ethiopia. Three household-based methods of identifying varietal adoption are tested against the benchmark of DNA fingerprinting: (A) elicitation from farmers with basic questions for the most widely planted variety; (B) farmer elicitation on five sweet potato phenotypic attributes by showing a visual-aid protocol; and (C) enumerator recording observations on five sweet potato phenotypic attributes using a visual-aid protocol and visiting the field. The reference being the DNA fingerprinting, about 30 percent of improved varieties were identified as local or non-improved, and 20 percent of farmers identified a variety as local when it was in fact improved. The variety names given by farmers delivered inconsistent and fuzzy varietal identities. The visual-aid protocols employed in methods B and C were better than method A, but still way below the adoption estimates given by the DNA fingerprinting method. The findings suggest that estimating the adoption of improved varieties with methods based on farmer self-reports is questionable, and point toward a wider use of DNA fingerprinting, likely to become the gold standard for crop varietal identification.